Summary for policymakers of the global assessment report on biodiversity and ecosystem services of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services - Díaz, Sandra (2019)
Fil: Díaz, Sandra. Universidad Nacional de Córdoba. Instituto Multidisciplinario de Biología Vegetal; Argentina.